How artists see animals - Carroll, Colleen (New York : Abbeville Kids, a division of Abbeville Press, 2019)
"[This book] invites children to discover how Andy Warhol's rhinoceros recalls a prehistoric cave painting, how Frank Gehry turned a fish's sleek aquatic shape into architecture, and how Georgia O'Keefe captured a bird in flight using just a few curving lines"--Provided by publisher.
Kirkus Review, September 2019
Includes bibliographical references (p. 41-47).
3-6
3-6
Kirkus Review
Keywords: Animals in art -- Juvenile literature; Art appreciation -- Study and teaching (Elementary) -- Juvenile literature; Interdisciplinary approach in education -- Juvenile literature; Animals in art; Art appreciation -- Study and teaching (Elementary); Interdisciplinary approach in education; Animals in art; Art appreciation -- Study and teaching; Elementary education; Interdisciplinary approach in education